Individual and Social Aspects of Quality of Life of the Disabled in the Context of Arts Education - Vilkelienė, Aldona; Kulikauskienė, Karolina (Pedagogika, 2014)
This paper examines the problem of quality of life that scientists explain in the very different ways: economic, medical, pedagogical-psychological and artistic therapeutic. The national documents and scientific research papers note that the social area – culture, science, environment - occupy a prominent place in the quality of life assessment, so there is a need to explore the quality of life in social environment, in conjunction not only with the individual’s economic and health status, but also with his personal features, cultural environment and education. The expression of quality of life for people with disabilities in the context of arts education was examined very fragmentary (Hays, Minichiello, 2005; Murphy, 2003); therefore the objective of the article is to analyze individual and social aspects of quality of life and to reveal the expression of its characteristics in the context of arts education. Subjective individual experiences, self-assessment, ability to realize one’s potential, sense of happiness and security complement the psychological satisfaction scale in the aspect, meaningful for the person. Mentally retarded young people who find it difficult to adequately express their emotions or to recognize them, often become incomprehensible to others, they lose opportunities to interact as valuable partners, their quality of life becomes worse. However, when analyzing the results of research, it follows, that positive emotions, social interactions and assessment of identity during artistic activity is one of the most important meanings of quality of life of the person. Identity, or self-perception, as a person belonging to a certain group, holding a certain status or capable of conveying certain values, can be developed by strengthening of national identity, which is revealed in the ethnic culture. Folk songs, dances, traditional crafts, ethnic symbols and rituals, as well as the other traditional activities, are the time-tested spiritual experience of the nation, by intonations and content close to the human nature: the lullabies intonation, simple rhythms. Hereby, in the context of special arts education, the content, related to the traditions and values, that are still alive in the family, school, community, expands the range of emotions, the limits of cooperation, and at the same time, the quality of life.